2017
DOI: 10.1016/j.eurpsy.2017.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Disorders Among Adult ADHD Patients: Is Borderline Personality Disorder as Common as we Expect?

Abstract: IntroductionPatients with Attention Deficit/Hyperactivity Disorder (ADHD) have shown a high risk to develop a DSM cluster B (i.e., Borderline, OR = 13.16; Antisocial, OR = 3.03; Narcissistic, OR = 8.69) and DSM Avoidant personality disorder (OR = 9.77). Similarly, higher rates of DSM cluster B personality disorder were found among adult ADHD patients (6-25%) than general population. Although some authors investigated the prevalence of personality traits and disorders among adult ADHD patients, no studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This study included several mediating variables [marital status ( Botterill et al., 2016 ; Harpin, 2005 ), employment ( Feigelman et al., 1995 ; Harpin, 2005 ), smoking status ( McClernon & Kollins, 2008 ; Petry & Oncken, 2002 ), alcohol dependence ( del Pino-Gutiérrez et al., 2017 ; Wilens, 2004 ), drug use ( Wareham & Potenza, 2010 ; Wilens, 2004 ), IQ ( Biederman et al., 2012 ; Rai et al., 2014 ), common mental disorders (CMDs; depressive episode and/or anxiety disorders) ( Becker et al., 2015 ; Clarke, 2006 ; Davidsson et al., 2017 ), BPD traits ( Matthies & Philipsen, 2014 ; Oliva et al., 2017 ), perceived stress and the number of stressful life events ( Biback & Zack, 2015 ; Vrijsen et al., 2017 ), and impulsivity ( Hodgins & Holub, 2015 ; Miller et al., 2010 )], which may be associated with or be the consequence of ADHD, and also be the cause of gambling problems. Sociodemographic variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included several mediating variables [marital status ( Botterill et al., 2016 ; Harpin, 2005 ), employment ( Feigelman et al., 1995 ; Harpin, 2005 ), smoking status ( McClernon & Kollins, 2008 ; Petry & Oncken, 2002 ), alcohol dependence ( del Pino-Gutiérrez et al., 2017 ; Wilens, 2004 ), drug use ( Wareham & Potenza, 2010 ; Wilens, 2004 ), IQ ( Biederman et al., 2012 ; Rai et al., 2014 ), common mental disorders (CMDs; depressive episode and/or anxiety disorders) ( Becker et al., 2015 ; Clarke, 2006 ; Davidsson et al., 2017 ), BPD traits ( Matthies & Philipsen, 2014 ; Oliva et al., 2017 ), perceived stress and the number of stressful life events ( Biback & Zack, 2015 ; Vrijsen et al., 2017 ), and impulsivity ( Hodgins & Holub, 2015 ; Miller et al., 2010 )], which may be associated with or be the consequence of ADHD, and also be the cause of gambling problems. Sociodemographic variables.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding intelligence, children with ADHD have been reported to have lower intelligence quotient (IQ) than control subjects ( Biederman, Fried, Petty, Mahoney, & Faraone, 2012 ), and in turn, people with lower IQ are at a higher risk of problem gambling ( Rai et al., 2014 ). In addition, there has been some literature showing that ADHD is strongly associated with mental disorders and BPD ( Becker, Langberg, Evans, Girio-Herrera, & Vaughn, 2015 ; Davidsson et al., 2017 ; Matthies & Philipsen, 2014 ), while some authors have suggested that these disorders might be key players in the subsequent onset of gambling addiction ( Clarke, 2006 ; Oliva et al., 2017 ). Finally, stressful life events and stress are frequently found in people with ADHD ( Vrijsen et al., 2017 ), and they are often considered as strong motivations for gambling ( Biback & Zack, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al found that the risk of developing a personality disorder is increased in the individuals with ADHD. In his study he showed that the most frequent were borderline, antisocial, avoidant and narcissistic personality disorders 11,12 .…”
Section: Original Papermentioning
confidence: 99%
“…Th ere have been many correlations in literature regarding ADHD in the adult population and personality disorders, the relationship being explained in multiple ways. An aspect that can be discussed is the fact that in many cases this symptomatology that persists longitudinally with possible fl uctuations can be complicated by the emergence of other comorbidities 4,5 .…”
Section: Introductionmentioning
confidence: 99%